A semi-quantitative multi-hazard risk assessment framework for European coastal urban areas - Rui Figueiredo; Raymundo Rangel-Parra; Gianbattista Bussi; Paola Ceresa; Gabriele Coccia; Mario L.V. Martina (Geomatics, Natural Hazards & Risk)
Coastal cities are increasingly exposed to a wide range of hydro-meteorological and climate-related hazards and their negative consequences. Developing disaster risk assessments to support risk management activities in these areas is therefore a critically important but challenging task, due to the diversity of processes involved and associated data requirements. Semi-quantitative, i.e. index-based assessments can be instrumental in addressing these issues: by trading off some detail in the representation of risk for simplicity in the underlying data and methods, it becomes possible to assess, compare, and easily communicate risk for various sectors, hazards, and locations. In this context, the present article presents a new semi-quantitative, GIS-based multi-hazard risk assessment framework for coastal urban areas. The framework uses various large-scale datasets and state-of-the-art risk modelling concepts to provide risk scores for six perils in European coastal cities: fluvial flooding, coastal flooding, extreme precipitation, landslide, heat wave, and coastal erosion. An application is presented for the risk assessment of ten case-study areas, illustrating the potential of the proposed framework for identifying the most pressing risks for each area and supporting the prioritization of more detailed quantitative risk assessments for specific cities, sectors and/or hazards, based on which risk mitigation measures can be defined.